Lobar lung transplantation—Is it comparable with standard lung transplantation?. (17th June 2014) - Slama, Alexis; Ghanim, Bahil; Klikovits, Thomas; Scheed, Axel; Hoda, Mir A.; Hoetzenecker, Konrad; Jaksch, Peter; Matilla, Jose; Taghavi, Sharokh; Klepetko, Walter; Aigner, Clemens
Summary Lobar lung transplantation is used mainly for urgent small recipients who are less likely to obtain size matched lungs in due time. Only limited numbers have been published, and we herewith report the largest series of lobar‐LuTX. We analyzed our LuTX database from 1/2001 to 12/2012 and compared the outcome of lobar‐LuTX recipients with those receiving standard LuTX. Seven hundred and seventy‐eighty LuTX (group 1) were performed either in standard technique by implanting the whole lungs (n = 539) or with downsizing by wedge resection of the right middle lobe and/or the left lingula (n = 239). One hundred and thirty‐eight LuTX were performed in lobar technique (group 2) to overcome more pronounced size discrepancies. Patients in group 1 had a different spectrum of diagnoses and were less frequently bridged to LuTX (P < 0.001). Intubation time, ICU stay, and hospital stay were shorter in group 1 (P < 0.001). One‐year survival was 84.8% vs. 65.1%, and 5‐years survival 69.9% vs. 54.9% (P < 0.001). In multivariate analyzes, procedure, diagnosis, and pre‐operative bridging were shown to be significant prognostic factors in survival. Early postoperative outcome in Lobar LuTX was significantly inferior to standard LuTX recipients. However, survival rates of successfully dismissed patients were comparable with standard LuTX (P = 0.168); thereby, Lobar‐LuTX remains an important option in the management of urgent small recipients.